Remediating Distances, Presentation of IMG Journal 3/2020 (diségno, 2021)
IMG Journal () is an emerging scientific journal part of the network of IMG initiatives ( (accessed 2021, May 14),–inaugurated by the first international conference held in 2017 at the University Campus in Bressanone. It represents a meeting point and an interdisciplinary academic exchange aimed to explore and discuss, from different points of view, the intersectional space between images, imagery and imagination (read more).